2012
DOI: 10.1515/hf.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia addition to alkaline copper quaternary wood preservative solution on the distribution of copper complexes and leaching

Abstract: The effects of ammonia (NH 3 ) addition to monoethanolamine (Mea)-based alkaline copper quaternary (ACQ) on the predicted distribution of cupric (Cu 2q ) species in solution and copper leaching from treated wood were investigated. Addition of ammonia in higher proportions reduced the amount of neutral copper-Mea complex at high pH and increased the amounts of divalent copper-NH 3 complexes. At lower pH, the amounts of high-ligand copper-Mea complexes were reduced. These effects should promote better fixation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…By contrast, the toxicity of heavy metals and other chemicals used as wood preservatives are also a matter of serious health and environmental concern [208][209][210][211]. The intense research activities on developing and testing less problematic protective systems demonstrate the urgent need for innovation in this field [212][213][214][215][216][217][218][219][220]. As the antagonistic properties were evolved in competition with other wood destroyers-such as wood-rotting and sap-staining fungi, or other molds-the expectation is justified that the Trichoderma isolated from wood does have the ability to effectively inhibit wood-damaging fungi.…”
Section: Wood Preservationmentioning
confidence: 99%
“…By contrast, the toxicity of heavy metals and other chemicals used as wood preservatives are also a matter of serious health and environmental concern [208][209][210][211]. The intense research activities on developing and testing less problematic protective systems demonstrate the urgent need for innovation in this field [212][213][214][215][216][217][218][219][220]. As the antagonistic properties were evolved in competition with other wood destroyers-such as wood-rotting and sap-staining fungi, or other molds-the expectation is justified that the Trichoderma isolated from wood does have the ability to effectively inhibit wood-damaging fungi.…”
Section: Wood Preservationmentioning
confidence: 99%
“…Studies have demonstrated that micronized copper azole and micronized copper quaternary comprising wood preservatives showed better performance compared to formulations using soluble copper [8,9,18]. Soil pH and composition have drastic effects on the protective ability of MC [9,19], but overall, MC particles show much lower leaching compared to soluble copper formulations due to the reservoir effect [20]. The same effect was confirmed for other particle-based wood preservatives.…”
Section: Introductionmentioning
confidence: 88%